OMNIBUS LAW: DOMINASI KEKUASAAN EKSEKUTIF DALAM PEMBENTUKAN LEGISLASI - Suntoro, Agus; Nureda, Kania Rahma (Faculty of Law, Parahyangan Catholic University, 2022)
President Joko Widodo on November 2, 2020 signed Law No. 11 of 2020 concerning Job Creation, which is known to the public as the omnibus law. The omnibus law is a simplification mechanism for 79 (seventy nine) laws aimed at encouraging investment and job creation. Various aspirations and objections from the public, in terms of substance and formality were not taken seriously by the government and parliament, instead there were arrests, detentions and suggested a judicial review at the Constitutional Court. The presence of the omnibus law will increase regulatory obesity because it imposes a delegation of 450 (four hundred and fifty) arrangements and further emphasizes the dominance of executive power. The research method used is qualitative with descriptive presentation. Primary legal materials are collected through inquiries from members of parliament and academics/experts, while secondary legal materials are based on reports, journals, books and regulations. This research concludes that: (a) the acceleration of the discussion of the Job Creation Law is influenced by the power of the President as the leader of the coalition whose membership reaches 74% in parliament; (b) the formation process is still problematic in the formal aspect, especially with the lack of public participation and transparency, but the omnibus law has become a new tradition in the formation of the state administration system; and (c) the Job Creation Law becomes an indicator of the domination and integralism of executive power and a reduction in legislative authority in drafting laws.